2008
DOI: 10.1080/08927010802254583
|View full text |Cite
|
Sign up to set email alerts
|

The biology of biofouling diatoms and their role in the development of microbial slimes

Abstract: Diatoms are a major component of microbial slimes that develop on man-made surfaces placed in the marine environment. Toxic antifouling paints, as well as environmentally friendly, fouling-release coatings, tend to be effective against most fouling organisms, yet fail badly to diatom slimes. Biofouling diatoms have been found to tenaciously adhere to and colonise even the most resistant of artificial surfaces. This review covers the basic biology of fouling marine diatoms, their mechanisms of adhesion and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
181
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(190 citation statements)
references
References 67 publications
3
181
0
6
Order By: Relevance
“…Cocconeis exhibits a heterovalvar morphology, each frustule being composed of a rapheless valve [exhibiting a sternum (¼ pseudoraphe)] and a raphe valve. This type of morphology is described as being 'monoraphid' (Kobayasi & Nagumo, 1985;Round et al, 1990;De Stefano & Romero, 2005;Molino & Wetherbee, 2008). One of the most important characters of Cocconeis and related genera is the structure of the cingulum (Holmes et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Cocconeis exhibits a heterovalvar morphology, each frustule being composed of a rapheless valve [exhibiting a sternum (¼ pseudoraphe)] and a raphe valve. This type of morphology is described as being 'monoraphid' (Kobayasi & Nagumo, 1985;Round et al, 1990;De Stefano & Romero, 2005;Molino & Wetherbee, 2008). One of the most important characters of Cocconeis and related genera is the structure of the cingulum (Holmes et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Diatoms are unicellular algae in which the protoplast is enclosed in a silica case (the frustule) composed of overlapping halves or 'valves'. Adhesion of raphid diatoms is a complex process that is mediated by the secretion of extracellular polymeric substances (EPS), comprising a range of proteoglycans, through one or two slits in the silica cell wall called raphes (see review by Molino and Wetherbee 2008). Contact with the substratum initiates a number of processes that facilitate primary adhesion and gliding motility (Molino and Wetherbee 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The attached diatoms played a signifi cant role in the development of the subsequent macrofouling community (Joint et al, 2002;Huang et al, 2007;Qian et al, 2007). Only a few studies have focused on the community of biofi lm diatoms in the marine environment (Molino and Wetherbee, 2008;Sweat and Johnson, 2013). Recent reports covered the infl uence of substrate properties and anti-fouling coatings on the diatom community (Cao et al, 2011;Dobretsov and Thomason, 2011;Zargiel et al, 2011;Dobretsov et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, diatoms play very important roles in the settlement of fouling animals. Previous studies have also shown that antifouling coatings that were once effective against most fouling organisms now largely fail to inhibit diatom settlement (Molino and Wetherbee, 2008). Therefore, more and more attention has been paid to the study of fouling diatom community structure.…”
Section: Introductionmentioning
confidence: 99%